2015
DOI: 10.1017/cem.2014.64
|View full text |Cite
|
Sign up to set email alerts
|

Emergency medicine as a primary specialty—French emergency medicine residents’ attitudes

Abstract: Emergency medicine (EM) has been a fellowship program (supra-specialty) in France since 2004. Even though the program can be accessed after completion of one of several primary specialties, the vast majority (97%) of its residents enter the program after having completed training in family medicine. A change to develop a primary EM specialty is being discussed. Our objective was to assess French residents and young EM physicians' attitudes toward EM as a primary specialty. We conducted a brief cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In Brazil, a Short-Form Health Survey Questionnaire (SF-36) showed that emergency physicians had worse scores in the pain domain (an aspect of psychological health). [613] Such mental burdens and compassion fatigue were similar across physician specialties (including surgical and medical) in the USA and were found to lead to traumatic stress. [14] A recent pilot study from Canada examining the quality of work life (QWL) showed that emergency department physician in rural emergency departments have an average QWL with lower QWL in the subscales “support offered to employees” and working conditions reflected in the subscale “human and material resources.”[15] It was concluded that these domains possibly constitute psychosocial risk factors, which suggests the need for interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, a Short-Form Health Survey Questionnaire (SF-36) showed that emergency physicians had worse scores in the pain domain (an aspect of psychological health). [613] Such mental burdens and compassion fatigue were similar across physician specialties (including surgical and medical) in the USA and were found to lead to traumatic stress. [14] A recent pilot study from Canada examining the quality of work life (QWL) showed that emergency department physician in rural emergency departments have an average QWL with lower QWL in the subscales “support offered to employees” and working conditions reflected in the subscale “human and material resources.”[15] It was concluded that these domains possibly constitute psychosocial risk factors, which suggests the need for interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to former regimens, the primary specialty allows emergency medicine residents to be fully trained on the wide range of clinical situations we face in the emergency department (ED) but also in emergency medical communication centers (EMCC, i.e. medical dispatch centers, SAMU in French) or in mobile intensive care units (MICU) [2,3].…”
mentioning
confidence: 99%